Proline-Rich Antimicrobial Peptides in Medicinal Maggots of Lucilia sericata Interact With Bacterial DnaK But Do Not Inhibit Protein Synthesis - Cytryńska, Małgorzata; Rahnamaeian, Mohammad; Zdybicka-Barabas, Agnieszka; Dobslaff, Kristin; Züchner, Thole; Sacheau, Guénaël; Innis, C. Axel; Vilcinskas, Andreas (Frontiers in Pharmacology, 2020)
In the search for new antibiotics to combat multidrug-resistant microbes, insects offer a rich source of novel anti-infectives, including a remarkably diverse array of antimicrobial peptides (AMPs) with broad activity against a wide range of species. Larvae of the common green bottle fly Lucilia sericata are used for maggot debridement therapy, and their effectiveness in part reflects the large panel of AMPs they secrete into the wound. To investigate the activity of these peptides in more detail, we selected two structurally different proline rich peptides (Lser-PRP2 and Lser-PRP3) in addition to the α-helical peptide Lser-stomoxyn. We investigated the mechanism of anti-Escherichia coli action of the PRPs in vitro and found that neither of them interfered with protein synthesis but both were able to bind the bacterial chaperone DnaK and are therefore likely to inhibit protein folding. However, unlike Lser-stomoxyn that permeabilized the bacterial membrane by 1% at the low concentration (0.25 µM) neither of the PRPs alone was able to permeabilize E. coli membrane. In the presence of this Lser-stomoxyn concentration significant increase in anti-E. coli activity of Lser-PRP2 was observed, indicating that this peptide needs specific membrane permeabilizing agents to exert its antibacterial activity. We then examined the AMPs-treated bacterial surface and observed detrimental structural changes in the bacterial cell envelope in response to combined AMPs. The functional analysis of insect AMPs will help select optimal combinations for targeted antimicrobial therapy.